2003
DOI: 10.1124/dmd.31.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoid Stimulation of Glutathione Transport by the 190-kDa Multidrug Resistance Protein 1 (MRP1)

Abstract: ABSTRACT:In tumor cells, the human multidrug resistance protein 1 (MRP1), confers resistance to a broad spectrum of anticancer agents. MRP1 is also expressed in many normal tissues where it acts as an ATP-dependent transporter of organic anions. , respectively. Chemosensitivity assays with control-transfected and MRP1-transfected HeLa cell lines showed that the IC 50 values for apigenin, naringenin, genistein, and quercetin were similar, demonstrating that overexpression of MRP1 does not confer resistance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 25 publications
4
91
1
Order By: Relevance
“…Reduced glutathione was proven to be a poor substrate of MRP1 [79,87], but its transport is stimulated by bioflavonoids and verapamil by increasing the apparent affinity of the transporter for GSH [82,88]. In contrast, GSSG by itself was found to be a substrate with an apparent K m value of around 100 μM [79].…”
Section: Dual Role Of Mrp1 In the Physiological Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced glutathione was proven to be a poor substrate of MRP1 [79,87], but its transport is stimulated by bioflavonoids and verapamil by increasing the apparent affinity of the transporter for GSH [82,88]. In contrast, GSSG by itself was found to be a substrate with an apparent K m value of around 100 μM [79].…”
Section: Dual Role Of Mrp1 In the Physiological Barriersmentioning
confidence: 99%
“…These are exemplified by estrone 3-sulfate, 4-(methylnitrosami- [84,127,133]. In contrast to these substrates, certain compounds, such as verapamil and bioflavonoids, are not transported by MRP1 but they enhance the MRP1-mediated transport of GSH [82,88].…”
Section: Handling Of Substratesmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the binding of two MRP1-specific modulating agents, agosterol A and LY475776, is dependent on GSH (Ren et al, 2001;Mao et al, 2002). Interestingly, xenobiotics such as verapamil and several dietary flavonoids (including the flavone apigenin), stimulate GSH transport by MRP1 up to 4-fold without being transported themselves (Loe et al, 2000;Leslie et al, 2001cLeslie et al, , 2003. Overall, the interaction between MRP1 and GSH is complex and presently is not well understood.…”
mentioning
confidence: 99%
“…It was later found that some flavonoids have the same effect on MRP1 [40]. Hydroxychalcones, the precursors of flavonoids, were also found to induce GSH depletion, although the MRP(s) involved remain to be identified [41].…”
Section: Mrps and Glutathionementioning
confidence: 99%